0.2 λ0 Thick Adaptive Retroreflector Made of Spin‐Locked Metasurface. Issue 39 (20th August 2018) - Yan, Libin; Zhu, Weiming; Karim, Muhammad Faeyz; Cai, Hong; Gu, Alex Yuandong; Shen, Zhongxiang; Chong, Peter Han Joo; Kwong, Dim‐Lee; Qiu, Cheng‐Wei; Liu, Ai Qun
Abstract: The metasurface concept is employed to planarize retroflectors by stacking two metasurfaces with separation that is two orders larger than the wavelength. Here, a retroreflective metasurface using subwavelength‐thick reconfigurable C‐shaped resonators (RCRs) is reported, which reduces the overall thickness from the previous record of 590 λ0 down to only 0.2 λ0 . The geometry of RCRs could be in situ controlled to realize equal amplitude and phase modulation onto transverse magnetic (TM)‐polarized and transverse electric (TE)‐polarized incidences. With the phase gradient being engineered, an in‐plane momentum could be imparted to the incident wave, guaranteeing the spin state of the retro‐reflected wave identical to that of the incident light. Such spin‐locked metasurface is natively adaptive toward different incident angles to realize retroreflection by mechanically altering the geometry of RCRs. As a proof of concept, an ultrathin retroreflective metasurface is validated at 15 GHz, under various illumination angles at 10°, 12°, 15°, and 20°. Such adaptive spin‐locked metasurface could find promising applications in spin‐based optical devices, communication systems, remote sensing, RCS enhancement, and so on. Abstract : A subwavelength‐thick, spin‐locked planar retroreflector is realized using an adaptive metasurface composed of reconfigurable C‐shaped resonators (RCRs). The geometry of the RCRs can be in situ controlled to realize equal amplitude and phase modulation onto transverse magnetic (TM)‐polarized and transverse electric (TE)‐polarized incidences, which enables spin‐locked retroreflection under various illumination angles at 10°, 12°, 15°, and 20°.